2022
DOI: 10.3389/fpsyg.2022.951861
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ethical Leadership on Employees’ Green Innovation Behavior: A Mediating-Moderating Model

Abstract: To enhance environmental protection and sustainable development, green innovation (GI) is an inevitable choice for enterprises. This study incorporates social identity theory and social learning theory to explore the impact of ethical leadership on employee GI behavior. In addition, this study also examines the mediating effects of green organizational identity (GOI) and the moderating role of strategic flexibility (SF). Using the structural equation modeling, an empirical survey was conducted among 300 Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 78 publications
0
6
0
1
Order By: Relevance
“…This is consistent with results from previous studies. Yang & Liu (2022) found EL positively affects employees' green innovative behavior. Also, Crosley (2014) explored the possible relationship between EL and IC and found significant positive correlations between the two.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with results from previous studies. Yang & Liu (2022) found EL positively affects employees' green innovative behavior. Also, Crosley (2014) explored the possible relationship between EL and IC and found significant positive correlations between the two.…”
Section: Discussionmentioning
confidence: 95%
“…This finding echoes prior research that also found EL to stimulate innovation. Numerous studies have shown that ethical leaders, by promoting trust, openness, and a commitment to values, contribute to a conducive environment for innovative thinking and practices (Şengüllendi et al, 2023;Yang & Liu, 2022). As shown earlier, high power distance means employees look to leaders for guidance more than individualistic cultures (Taqi, 2020).…”
Section: Hypotheses Testingmentioning
confidence: 94%
“…Por otro lado; el emprendimiento es entendido como la capacidad producto de la movilización de destrezas y cualidades que hacen posible la creación, puesta en marcha y desarrollo de proyectos o el logro de objetivos sociales y personales (Yang y Liu, 2022).…”
Section: Resultsunclassified
“…This study draws inspiration from previous studies such as [34,35], who narrated the connection between ethical behavior and green growth. Having established the stationarity of the dataset, we follow Poveda [36]; Abbate et al [37,38]; Costa and Matias, [39]; Lee [40]; Shakeel and Ahmed [41]; Fujii and Managi [42]; Zhang and Jiang [43] and Li et al [33], and employ panel corrected standard errors model to examine the role of ethics (i.e., ethical behavior) on green growth.…”
Section: Panel Analysismentioning
confidence: 99%